1999
DOI: 10.1097/00005650-199901000-00014
|View full text |Cite
|
Sign up to set email alerts
|

When Asked, Patients Tell

Abstract: These findings suggest patients are not less willing to disclose health risks to a research assistant knowing that this information would be shared with their physician and that a number of assessment methods can effectively elicit patient disclosure. Potentially small increases in risk disclosure must be weighed against other factors, such as cost and convenience, in determining which method(s) to use in different health care settings.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
13
2

Year Published

2001
2001
2015
2015

Publication Types

Select...
6
2

Relationship

2
6

Authors

Journals

citations
Cited by 102 publications
(16 citation statements)
references
References 25 publications
1
13
2
Order By: Relevance
“…This bias may have been further enhanced by the possible reporting of risky behaviors to providers through Cueing Sheets. We are unable to validate participants' self-reports, but remain convinced that computerized questionnaires yield more disclosure of sensitive topics than do other, traditional methods, such as face-to-face interviews or paper questionnaires [33], [34]. Although our previous research found that sharing risk information with providers did not inhibit patients' disclosure of sensitive behaviors [33], we have no evidence to deny this occurring in the present study.…”
Section: Discussioncontrasting
confidence: 69%
“…This bias may have been further enhanced by the possible reporting of risky behaviors to providers through Cueing Sheets. We are unable to validate participants' self-reports, but remain convinced that computerized questionnaires yield more disclosure of sensitive topics than do other, traditional methods, such as face-to-face interviews or paper questionnaires [33], [34]. Although our previous research found that sharing risk information with providers did not inhibit patients' disclosure of sensitive behaviors [33], we have no evidence to deny this occurring in the present study.…”
Section: Discussioncontrasting
confidence: 69%
“…39,5153 A variety of methods are effective for eliciting sensitive health risks such as IPV. 54 In our study parents may have left the IPV screening questions blank for a number of reasons. Mothers may fear for their own safety and the safety of their children should disclosure of IPV become known to the perpetrator.…”
Section: Commentmentioning
confidence: 99%
“…They can also be tailored to individual users through the use of integrated risk assessments. This tailoring, plus enhanced anonymity, allows participants to feel more comfortable with computer-based assessments of sensitive information, like high-risk sex or drug use [19], leading to greater disclosure of stigmatized behaviors [20, 21]. CBIs are also delivered with very high fidelity across time and location, increasing their probability of success [16, 22].…”
Section: Introductionmentioning
confidence: 99%